2018
DOI: 10.1364/boe.9.001164
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved diffuse reflectance spectroscopy endoscopic sensing with custom Si photodetectors

Abstract: Early detection and surveillance of disease progression in epithelial tissue is key to improving long term patient outcomes for colon and esophageal cancers, which account for nearly a quarter of cancer related mortalities worldwide. Spatially resolved diffuse reflectance spectroscopy (SRDRS) is a non-invasive optical technique to sense biological changes at the cellular and sub-cellular level that occur when normal tissue becomes diseased, and has the potential to significantly improve the current standard of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Development and evaluation of MC populated LUT inverse models for the extraction of colon optical properties using the MEOS probe were based on the system in Fig. 1, using initial measured phantom and MC forward modeling studies previously reported [18].…”
Section: Description Of Lut Optical Property Extraction Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Development and evaluation of MC populated LUT inverse models for the extraction of colon optical properties using the MEOS probe were based on the system in Fig. 1, using initial measured phantom and MC forward modeling studies previously reported [18].…”
Section: Description Of Lut Optical Property Extraction Methodsmentioning
confidence: 99%
“…However, the reliance of conventional DRS systems on optical fibers for reflectance collection limits system performance, limits scalability, and constrains the design options. In contrast, custom thin film silicon (Si) photodetectors (PDs) offer a high performance, scalable, and highly customizable alternative to optical fibers for reflectance collection in tissue DRS applications [14][15][16][17][18]. Si PDs improve performance over optical fibers since they have higher numerical apertures (NAs) and collect light from a larger fraction of the probe surface, they are highly scalable due to Si manufacturing technology, they can be geometrically optimized for specific applications, they can be implemented on a variety of substrates, including flexible or conformal, and they can be implemented in the instrument channel or as an attachment to an endoscope.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations